Efecto del grado de contaminación microbiana en los mostos utilizados en la producción de alcohol artesanal en los diferentes fábricas del sector La Maná. - Escobar Cadena, Ruth Soraya (2018)
The present project tries to determine the effect of the degree of microbial contamination in the mosto used in the production of artisanal alcohol in the different factories of La Maná sector where five artisanal alcohol processors are studied. This study of variables was done out ( Brix, pH, Temperatures and Real Alcohol) during the process of fermentation and distillation of alcohol that has a maximum duration of two days. The variables are controlled in three times in the points of the vats for every four hours until the fermentation process is finished. The distillation process was founded by measuring the alcoholic levels of the alcoholic bodies of the artisanal alcohol elaboration obtaining statistical results where the °Brix at the beginning of the process were high and ended with low results while the pH in its initial stage of fermentation is high and in the final process of the fermentation is low therefore the actual alcohol was increasing from the beginning of the fermentation process until the end obtaining good yields. A sample of the juice must was taken and placed to the laboratories of the Technical University of Cotopaxi where the isolation and selection of the yeasts was carried out. It was found in the fermentation processes of artisanal alcohol in La Maná area. Laboratory studies were carried out that applied an isolation technique for its isolation in sterile media with an Agar (Sabouraud dextrose). The incubation process was carried out at 32 ° C for 24 hours and the type of yeast that was found in the mosto by its fermentor, this guaranteed a better result when identifying the yeasts that fermented in the juice of the cane juice, identified the physical and chemical factors that caused a contamination that affected the final performance of the alcohol in its natural environment. Finally, with these studies refers to the percentage of contamination, its yield and the type of yeast found in the fermentation process that helped the transformation of sugar cane juice into alcohol obtained by distillation.